When is it wrong to eat animals? The relevance of different animal traits and behaviours. (18th January 2021) - Leach, Stefan; Sutton, Robbie M.; Dhont, Kristof; Douglas, Karen M.
Abstract: Research suggests that animals' capacity for agency, experience, and benevolence predict beliefs about their moral treatment. Four studies built on this work by examining how fine‐grained information about animals' traits and behaviours (e.g., can store food for later vs. can use tools) shifted moral beliefs about eating and harming animals. The information that most strongly affected moral beliefs was related to secondary emotions (e.g., can feel love), morality (e.g., will share food with others), empathy (e.g., can feel others' pain), social connections (e.g., will look for deceased family members), and moral patiency (e.g., can feel pain). In addition, information affected moral judgements in line with how it affected superordinate representations about animals' capacity for experience/feeling but not agency/thinking. The results provide a fine‐grained outline of how, and why, information about animals' traits and behaviours informs moral judgements.